Blink reflex: comparison of latency measurements in different human races - Paulo Andre Teixeira Kimaid; Luiz Antonio Lima Resende; Heloisa Amélia de Lima Castro; Fausto Bérzin; Amilton Antunes Barreira (Arquivos de Neuro-Psiquiatria)
The blink reflex latencies and cephalometric indexes were analysed in 30 male volunteers from three different races, 10 white, 10 black, and 10 Oriental. Ages ranged from 15 to 59 years, height from 1,60 to 1,80 m, and weight from 60 to 80 kg. Blink reflexes were obtained after unilateral electric stimulation of the supraorbital nerve for quantitative analysis of 3 responses, early ipsilateral (R1), late ipsilateral (R2i) and late contralateral (R2c), obtained from the orbicularis oculi muscle. Cephalometric indexes were calculated by multiplying the ratio between the longer transverse and the longer sagital head diameters by 100. The R1, R2i and R2c latencies were consistent with other published papers revealing no differences between the different racial groups. The mean of the cephalometric indexes of each group were consistent with respective racial characteristics. This study revealed that there are no differences between R1, R2i and R2c latencies in the 3 different studied races.